Screening Public Private Partnership Projects as An Implementation of the Middle Path Theory in Indonesian Investment - Wahyu Agung Laksono; Prita Amalia; Adi Nurzaman (Journal of Law, Politic and Humanities, 2024)
Investment in Indonesia has existed since the colonial period, which then experienced developments in 1945, 1966, 1998, until the current reform era as outlined in Law Number 25 of 2007 concerning Investment. Investment activities are currently experiencing many developments, one of which is the presence of Government Cooperation with Business Entities as an alternative to infrastructure provision and management. However, this method is considered slow due to the screening project stage so that an analysis is needed regarding the origin of the stage through the middle path theory. This research uses legal research method with normative juridical approach. The research specification is descriptive analytical with legal interpretation analysis method. The data used is secondary data, consisting of primary, secondary, and tertiary legal materials. The results of this study show that the screening project stage consisting of needs analysis, compliance criteria, criteria for determining the value of money benefits, analyzing potential income, as well as recommendations and follow-up is an implementation of the principle of Government Cooperation with Business Entities, which explicitly shows that Indonesia uses the middle path theory. This is supported by the principles and content material of the project screening process which emphasizes the implementation of PPP in Indonesia based on government intervention and openness to Business Entities that will and/or enter into the PPP process. The middle path theory can serve as the basis for the implementation of PPP in terms of investment because it can attract investors to invest in Indonesia while at the same time suppressing the negative impact of investment activities, especially those carried out by multinational companies.